Extrinsic Motivation With Learning Achievements Student Of Nursing - Fitrah Suciah; Hamdana; Fatmawati (Comprehensive Health Care, 2019)
It must be stressed, that motivation is related to a goal. Learning outcomes will be optimal if there is motivation. Seeing the phenomena there are still many nursing students of Panrita Husada Bulukumba who obtained the final GPA while in the low category. Not only that, but there are also some complaints during the lecture process that are obtained from interviews with students who can interfere with the learning process. This study aims to determine the relationship of extrinsic motivation in terms of the role of the lecturer, the condition of the learning environment, the learning methods used by the lecturer, facilities, and infrastructure with the learning achievements of nursing students. This research uses a quantitative analytic design with a cross-sectional approach. The population in this study was 297 respondents. The number of samples was 100 respondents using a simple random sampling technique. The data collection method is done by using bivariate questionnaire sheets using Fisher's exact test. The results showed that there was a significant difference in proportion or relationship between the role of lecturers and learning achievement (p = 0.003), learning environment conditions and learning achievement (p = 0.043), lecturer learning methods and learning achievement (p = 0.029), facilities and infrastructure with learning achievement (p = 0.040). The conclusion is that there is a significant relationship between extrinsic motivation (the role of the lecturer, the condition of the learning environment, the lecturer learning method, and learning support facilities or facilities and infrastructure) with the learning achievement of the nursing student Panrita Husda Bulukumba.